Therapeutic effects of EGCG: a patent review. (2nd August 2016) - Chakrawarti, Leewanshi; Agrawal, Rishab; Dang, Shweta; Gupta, Sanjay; Gabrani, Reema
ABSTRACT: Introduction : Green tea contains polyphenolic flavanoids such as epigallocatechin-3- gallate (EGCG), epicatechin-3-gallate (ECG), epigallocatechin (EGC) and epicatechin (EC). EGCG is the most abundant and active compound in green tea. Extensive research has shown that it has significant antioxidant, anti-carcinogenic, anti-microbial, and neuroprotective properties and has therapeutic potential against various human diseases. Areas covered : This review focuses on the applications of EGCG alone, and in combination with other compounds, for the treatment of various types of cancers, metabolic, neurodegenerative, and microbial diseases, and discusses its mechanism of action in cell line and animal modesl. Recent advances, which include the use of nanoencapsulated EGCG to enhance the drug delivery and reduce cell toxicity, have also been discussed along with the comprehensive analysis of the specific granted patents associated with EGCG. Expert opinion : Under the current scenario, the role of EGCG as a therapeutic agent is being utilised and new approaches are being formulated to overcome the problem of stability and bioavailability of EGCG. EGCG and its derivatives could be used for the development of drugs for the treatment of cancer, as well as various microbial, metabolic, and neurodegenerative diseases.